2021
DOI: 10.18805/lr-4527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salicylic Acid on Plant Physiological and Yield Traits of Soybean

Abstract: Background: Salicylic acid (SA) is an endogenous plant growth regulator plays a vital role in plant growth, ion uptake, transport, interaction with other organisms and in the responses to environmental stress. The aim of the study was to find the effect of salicylic acid on chlorophyll content, superoxide dismutase and malondialdehyde level of leaves and seed yield parameters of soybean.Methods: Field trials were conducted during kharif 2018 and 2019 at ICAR-Indian Institute of Soybean Research, Indore farm (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Soybean has high water requirement during growth and is sensitive to water deficit. Drought has a significant negative impact on output, which has adversely affected soybean quality and yield worldwide (Kuchlan and Kuchlan, 2023). The data showed that the yield of different germplasm resources decreased by 40% ~ 70% under drought stress, which could cause a devastating disaster in soybean production (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Soybean has high water requirement during growth and is sensitive to water deficit. Drought has a significant negative impact on output, which has adversely affected soybean quality and yield worldwide (Kuchlan and Kuchlan, 2023). The data showed that the yield of different germplasm resources decreased by 40% ~ 70% under drought stress, which could cause a devastating disaster in soybean production (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Considering various uses of soybean products, the projected demand for this grain will be 371.3 million metric tons in 2030 with a 1.8% annual growth rate (Siamabele, 2021). The development of higher yield potential soybean variety is the main focus for soybean breeders to ensure food security of this century (Kuchlan and Kuchlan, 2023). A narrow genetic base is the major threat to varietal improvements of soybean.…”
Section: Introductionmentioning
confidence: 99%